Value creation through project risk management. Issue 5 (July 2019) - Willumsen, Pelle; Oehmen, Josef; Stingl, Verena; Geraldi, Joana
Abstract: Risk management is a common and widely adopted project practice. Practitioners use risk management based on a common assumption that risk management adds value to projects. Yet, in the complex and ambiguous environment of a project, value is often subjective. If this is the case, then how do stakeholders perceive project risk management to create value? This paper presents a literature review and an empirical study of project risk management as a means of creating value. The empirical study is based on interviews, analyzed through qualitative analysis, to unravel the subjective value of project risk management. Specifically, we addressed how practitioners perceived the connection between project risk management practices and value creation. We found that stakeholders' perceptions of value played an important role in how value was created through project risk management. What a stakeholder perceives to be important, such as the prospective outcomes of a project, influences the perceived value of a given project risk management practice. The empirical findings indicate the need for a contextualized understanding of the value of project risk management, and thereby provide a more nuanced view of the variety of forms through which project risk management can create value. The findings question the "universal ideal" of PRM value creation portrayed in the academic and practitioner literature. Highlights: Portrays a holistic model of value creation through project risk management The findings open up the debate about previously suggested "best practices" in PRM Provides a critical view on current and further research on the actuality of risk management in projects Proposes how to understand the value of project risk management through a lens of value creation